Pou5f3.2‐induced proliferative state of embryonic cells during gastrulation of Xenopus laevis embryo. (14th December 2015) - Nishitani, Eriko; Li, Chong; Lee, Jaehoon; Hotta, Hiroyo; Katayama, Yuta; Yamaguchi, Masahiro; Kinoshita, Tsutomu
Abstract : POU class V (POU‐V) transcription factors play the important role in maintenance of pluripotency and cell differentiation. Pou5f3.2 (Oct25), one of Xenopus POU‐V transcription factors, shows the zygotic expression prior to gastrulation. In order to know the molecular mechanism of pou5f3.2 expression at gastrula stage, we examined a responsiveness of pou5f3.2 to Nodal signaling. Animal cap assay demonstrated that Xnr2 activates the gene expression of pou5f3.2 . In comparative analysis of the 5′‐flanking region of pou5f3.2 between Xenopus laevis and X. tropicalis, two conserved regions were detected within the flanking region. Reporter analyses showed that one of the conserved regions contained an enhancer region, which had several Smad2/3 and FoxH1 binding motifs. ChIP assay demonstrated that Smad2 binds to the enhancer region. These results suggest that Nodal signaling induces zygotic expression of pou5f3.2 at gastrula stage. To understand a role of pou5f3.2 in gastrula embryos, morpholino oligo DNA of pou5f3.2 was injected into the lateral side of one blastomere at the 2‐cell stage. The morphant embryos showed diminution of Xbra1 expression and gastrulation defect in the injection side, suggesting the essential role of pou5f3.2 at the gastrula stage. Xbra1 expression and gastrulation were also inhibited by injecting with the synthesized RNAs of pou5f3.2 . Furthermore, in the pou5f3.2 ‐injected embryo, gene expression of p27Xic1 was drastically suppressed, and the number of dividing cells increased in the injection side. These results suggest that one role of pou5f3.2 is to keep the embryonic cells in undifferentiated and proliferative state during gastrulation. Abstract : Pou5f3.2, one of Xenopus POU‐V transcription factors, is expressed under Nodal signaling and causes cell proliferation at gastrula stage.